The Inclusion of Environmental Education in Science Teacher Education - Bodzin, Alec M.; Shiner Klein, Beth.; Weaver, Starlin; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
In the coming decades, the general public will be required ever more often to understand complex environmental issues, evaluate proposed environmental plans, and understand how individual decisions affect the environment at local to global scales. Thus it is of fundamental importance to ensure that higher quality education about these ecological issues raises the environmental literacy of the general public. In order to achieve this, teachers need to be trained as well as classroom practice enhanced. This volume focuses on the integration of environmental education into science teacher education. The book begins by providing readers with foundational knowledge of environmental education as it applies to the discipline of science education. It relates the historical and philosophical underpinnings of EE, as well as current trends in the subject that relate to science teacher education. Later chapters examine the pedagogical practices of environmental education in the context of science teacher education. Case studies of environmental education teaching and learning strategies in science teacher education, and instructional practices in K-12 science classrooms, are included. This book shares knowledge and ideas about environmental education pedagogy and serves as a reliable guide for both science teacher educators and K-12 science educators who wish to insert environmental education into science teacher education. Coverage includes everything from the methods employed in summer camps to the use of podcasting as a pedagogical aid. Studies have shown that schools that do manage to incorporate EE into their teaching programs demonstrate significant growth in student achievement as well as improved student behavior. This text argues that the multidisciplinary nature of environmental education itself requires problem-solving, critical thinking and literacy skills that benefit students$1 (Bwork right across the curriculum.s
TO ENVIRONMENTAL EDUCATION -- The History and Philosophy of Environmental Education -- Professional Preparation for Science Teachers in Environmental Education -- Approaches to Environmental Education -- Environmental Education Within Early Childhood -- Environmental Education Service-Learning in Science Teacher Education -- Beyond Terra firma: Bringing Ocean and Aquatic Sciences to Environmental and Science Teacher Education -- ENVIRONMENTAL EDUCATION PEDAGOGY -- Promoting the Use of Outdoor Learning Spaces by K-12 Inservice Science Teachers Through an Outdoor Professional Development Experience -- Integrating Environmental Education Field Trip Pedagogy into Science Teacher Preparation -- (3z(BEeew! There$1 (Bs Dew on My Toes(3y(B: Common Characteristics of Preservice Elementary Teacher Learning in Environmental Education and Instructional Strategies for Science Teacher Educators -- Name That Plant! Overcoming Plant Blindness and Developing a Sense of Place Using Science and Environmental Education -- Place-based Inquiry: Advancing Environmental Education in Science Teacher Preparation -- Summer Methods in Summer Camps: Teaching Projects WILD, WET, and Learning Tree at an Outdoor Environmental Education Center -- Teachers Connecting Urban Students to their Environment -- Exploring Preservice Teachers$1 (BMental Models of the Environment -- Pedagogy, Environmental Education, and Context: Promoting Knowledge Through Concept Mapping -- Unraveling the Scientific, Social, Political, and Economic Dimensions of Environmental Issues Through Role-Playing Simulations -- Exploring Environmental Education Through Ecofeminism: Narratives of Embodiment of Science -- The Value of Nonformal Environmental Education-Based Professional Development in Preservice Science Teacher Preparation -- Using Environmental Education Project Curricula with Elementary Preservice Teachers -- Situated Learning in Environmental Education: Using Geospatial Technologies with Preservice Secondary Teachers -- Using Podcasting to Address Nature-Deficit Disorder -- Integrating Web-based Activities and Site-based Experiences to Investigate Environmental Issues.s
Keywords: Education; Science -- Study and teaching; Education; Science Education; Teaching and Teacher Education; Educational Technology